Girl goddess # 9 nine stories - Block, Francesca Lia 1962- (Joanna Cotler books, 1998)
In this collection of fresh, funky stories for girls, acclaimed author Francesca Lia Block uses her compelling voice to bring to life a wide range of uniquely individual characters. From lady ivory and alabaster duchess meeting their celebrity idol to La trying to come to grips with her mother's suicide, these girls speak directly to today's young readers and remind them that in every girl there is a goddess. Meet Tweetie Sweet Pea and Peachy Pie, Jacaranda and Rave and Desiree. Meet Lady Ivory and Alabaster Dutchess, who interview their favorite rock star, Nick Agate, only to discover the magic and power in themselves. Meet Tuck Budd, who is happy living in Manhattan with her two moms, Izzy and Anastasia, until she begins to wonder who her father is. Meet La, who faces the loss of her mother with an imaginary androgynous blue friend who lives in her closet. Zingingly bright and dreamily dark, full of wonder and gritty reality, these stories by acclaimed author Francesca Lia Block show the reader that in every girl there truly is a goddess. The cutting-edge author of Weetzie Bat once again breaks new ground with Girl Goddess #9, nine stories about girl goddesses of every age and shape and color and size, wearing combat boots and spiky hair or dressed all in white. One girl has two moms, another has no mother at all but a strange blue skinned creature that lives in her closet. One is a rock star groupie, another loves dancing and reading poetry and having picnics in the backyard when the moon is full. These are stories about girls discovering that the world is not a simple place and that there is more than one way to live-in Ms. Block's rich, lyrical language that fans have come to adore and that Sassy magazine called a dream